Effect of Landslide Surge on Pile Foundation of Overhead Vertical Wharf - Xiaolong Zhang; Junshuai Mu; Chengzhi Wang; Duoyin Wang (Advances in Civil Engineering)
Waves generated by landslides into water cause great harm to wharfs. Hence, the surge wave pressure generated by the landslide serves as an important reference for the structural design of wharfs in reservoir areas. In this study, a series of hydraulic model tests were performed to study the energy and wave pressure produced by the surge. According to wave pressure-time curves, the extreme values of sudden transient changes in wave pressure are obtained. The mechanism and influencing factors of surge wave pressure on vertical wharf buildings are expounded. On this basis, a formula to calculate the wave pressure exerted by landslide surge on the pile foundation of an overhead vertical wharf is developed. A large number of experiments show that the empirical formula is in good agreement with the experimental data.